PERANAN LEMBAGA ADAT DALAM PENYELESAIAN KONFLIK LAHAN PADA HUTAN ADAT DI DESA ENGKODE KECAMATAN MUKOK KABUPATEN SANGGAU - is, Ar; Lumangkun, Augustine; Nugroho.R, Joko (Universitas Tanjungpura, 2014)
The aims of this research are to identify and to reviewing the supporting factors of the costumary instutions role in completion of the land conflicts. This completion was done with formulating various strategies used SWOT analysis. The strategic internal factor such as human resources, physical, financial, organization and structure in completion of land conflict showed elements of strengths in indigenous land have influence value with estimation from highest (1,19) to lowest (0,714). Elements of weakness have influence value with estimation from highest (1,187) to lowest (0,774). The strategic factors exsternal are rise and fall of economic, chage of social and politic climate well as power of law, development of technology, changes in government policy, the geographical location on the role of customary instution on completion of indigenous forests land conflict with elements of opportunities have influence with estimation from highest (1,34) to lowest (0,91). Elements of therats have influence value with estimation from Â highest (1,23) to lowestÂ (0,03). Keywords: Traditional institutions, conflict, customary forest, local wisdom, forest communities.